Long-term outcome of patients with Ménière’s disease following cochlear implantation: a comprehensive outcome study with validated assessment tools - Yılmaz Topçuoğlu, Miray-Su; Plinkert, Peter K.; Praetorius, Mark; Euteneuer, Sara (European archives of oto-rhino-laryngology and head & neck, 2024)
Patients suffering from Ménière’s disease (MD) experience vertigo, and impairments in hearing and quality of life (QoL). This study aims to investigate the impact of cochlear implantation (CI) on various aspects affecting patients with MD.